Physico Chemical Analysis of Shilajatu (Shodhita, Marita and Satwapathita) - Shashi Rekha V,; R S Sarashetti, (International Journal of Ayurveda and Pharma Research, 2022)
Shilajatu analysis is conducted as it is rare, controversial and herbo mineral drug. Conventional literature reveals that only Shodana is sufficient enough and no need to go for further processes like Marana and Satwapatana. Unlike Rasaratna samuchhaya, the need for research on physical and chemical properties of Shilajatu is essential and unavoidable. Shilajatu is mineral pitch found in Himalaya rocks as exudations in the form of resin, hence the name Shilajatu. The works focuses on physical and chemical components present in four different forms of Shilajatu in the form of Raw, Shodhita, Marita, Satwapatita. The study is undertaken to assess organoleptic characters, pH, specific gravity, ash value, percentage of acid insoluble ash value and % of water soluble ash, moisture content, solubility in distilled water, and % of solubility. Now a day’s stressful lifestyle, unhealthy diet, polluted environment, extremely pressurized work culture have created havoc among people affecting their physical and mental health leading to Medho vridhi vikaras (Hyperlipidemia). Shilajatu when used with proper Anupana can cure many diseases as said in Charaka chikitsa stana. Analytical study reveals presence of Elements like K, Ca, O, Cl, S, Na, Mg, Si, Al, Pb and oxides like K2O, CaO, SO3, MgO, Na2O, Al2O3, SiO3, P2O5, PbO, CuO, Cl in all the samples. Phytochemicals flavonoids, tannins, steroids triterpenoids, saponin, proteins were present in raw and Shodhita shilajatu.